Neuronal Activity in the Rat Pulvinar Correlates with Multiple Higher-Order Cognitive Functions - Yang, Fang-Chi (Vision (Basel), 2020)
The pulvinar, also called the lateral posterior nucleus of the thalamus in rodents, is one of the higher-order thalamic relays and the main visual extrageniculate thalamic nucleus in rodents and primates. Although primate studies report the pulvinar is engaged under attentional demands, there are open questions about the detailed role of the pulvinar in visuospatial attention. The pulvinar provides the primary thalamic input to the posterior parietal cortex (PPC). Both the pulvinar and the PPC are known to be important for visuospatial attention. Our previous work showed that neuronal activity in the PPC correlated with multiple phases of a visuospatial attention (VSA) task, including onset of the visual stimuli, decision-making, task-relevant locations, and behavioral outcomes. Here, we hypothesized that the pulvinar, as the major thalamic input to the PPC, is involved in visuospatial attention as well as in other cognitive functions related to the processing of visual information. We recorded the neuronal activity of the pulvinar in rats during their performance on the VSA task. The task was designed to engage goal-directed, top–down attention as well as stimulus-driven, bottom–up attention. Rats monitored three possible locations for the brief appearance of a target stimulus. An approach to the correct target location was followed by a liquid reward. For analysis, each trial was divided into behavioral epochs demarcated by stimulus onset, selection behavior, and approach to reward. We found that neurons in the pulvinar signaled stimulus onset and selection behavior consistent with the interpretation that the pulvinar is engaged in both bottom–up and top–down visuospatial attention. Our results also suggested that pulvinar cells responded to allocentric and egocentric task-relevant locations.